(untitled) (Contemporary Journal of Social Science Review, 2025)
This essay critically examines Eugene O’Neill’s Long Day’s Journey into Night, a semi-autobiographical play that was published in 1956 after his death. Long Day’s Journey into Night is considered to be O’Neill’s masterpiece, and his attempt at coming to terms with a traumatic past. The play offers not only an examination of O’Neill’s life, but is also one of the earliest works to explore the important themes and dangers of substance abuse, addiction, and alcoholism when these matters were generally shunned from the public theater stage for fear of glamorizing them. O’Neill wanted the text to be published twenty-five years after his death; however, his widow decided to publish it just three years after he died. In this essay Mary Tyrone, a character based on O’Neill’s mother, will be analyzed from the perspective of Medical Humanism and Geopathology. Medical Humanism is an approach that seeks to develop a humanist understanding of characters in literature, and examine how illness affects them, while Geopathology (coined by Una Chaudhuri) is a term that stands for the analysis of locations and how they affect their residents in modern drama. Medical Humanism and Geopathology will be used in tandem to explore how the Tyrone summer house (Mary’s residence) impacts Mary’s addiction and illness in order to develop a comprehensive understanding of the character.